Aspergillus steynii and Aspergillus westerdijkiae as potential risk of OTA contamination in food products in warm climates. (April 2015) - Gil-Serna, Jessica; Patiño, Belén; Cortes, Laura; Gonzalez-Jaen, Maria Teresa; Vazquez, Covadonga
Abstract: Aspergillus steynii and Aspergillus westerdijkiae are the main ochratoxin A (OTA) producing species of Aspergillus section Circumdati . Due to its recent description, few data are available about the influence of ecophysiological factors on their growth and OTA production profiles. In this work, the effect of temperature (20, 24 and 28 °C) and water activity ( a w ) (0.928, 0.964 and 0.995) on growth, sporulation and OTA production by these fungi was examined in CYA and media prepared from paprika, green coffee, anise, grapes, maize and barley. Growth was positively affected by the highest temperature and a w values indicating that both species might be expected in warm climates or storage conditions. However, optimal growth conditions showed differences depending on the medium. OTA production was markedly affected by substrate and showed qualitative and quantitative differences. Both species, especially A. steynii, represent a great potential risk of OTA contamination due to their high production in a variety of conditions and substrates, in particular in barley and paprika-based media. Additionally, neither growth nor sporulation did result good indicators of OTA production by A. steynii or A. westerdijkiae ; therefore, specific and highly-sensitive detection methods become essential tools for control strategies to reduce OTA risk by these species. Highlights: Aspergillus steynii supposes a higher risk of OTA contamination than Aspergillus westerdijkiae . Paprika and barley-based media support the highest OTA production by both species. High temperature and a w levels induce fungal growth and OTA production. Fungal growth and sporulation are not good indicators of OTA production.